2009
DOI: 10.1029/2008jb005869
|View full text |Cite
|
Sign up to set email alerts
|

Sudden drop of seismic velocity after the 2004 Mw 6.6 mid‐Niigata earthquake, Japan, observed with Passive Image Interferometry

Abstract: [1] Passive Image Interferometry (PII) is a seismological method employing ambient seismic noise to monitor the temporal evolution of mean shear wave velocity within the Earth. First, the elastic Green's tensor between two seismometers is computed from the cross correlation of seismic noise recorded during a certain period. Second, the constructed seismograms of different time periods are treated as earthquake multiplets, and small time shifts in their coda are used to invert a relative change in mean shear wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
139
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(172 citation statements)
references
References 48 publications
(114 reference statements)
9
139
0
Order By: Relevance
“…Temporal changes have been successfully detected directly after large earthquakes as a sudden drop in seismic velocity and a slow recovery afterwards (Brenguier et al 2008a;Wegler et al 2009;Richter et al 2014). Monitoring of active volcanoes showed a drop in seismic velocity before eruptions (Brenguier et al 2008b;Sens-Schönfelder et al 2014).…”
Section: Introductionmentioning
confidence: 90%
“…Temporal changes have been successfully detected directly after large earthquakes as a sudden drop in seismic velocity and a slow recovery afterwards (Brenguier et al 2008a;Wegler et al 2009;Richter et al 2014). Monitoring of active volcanoes showed a drop in seismic velocity before eruptions (Brenguier et al 2008b;Sens-Schönfelder et al 2014).…”
Section: Introductionmentioning
confidence: 90%
“…With data from a very dry region in Chile, Richter et al (2014) derived a model for the annual variations based on thermally induced stress described in more detail in Section 3.1.1. Velocity drops after large earthquakes followed by a slow recovery were detected by Rubinstein & Beroza (2004a), Li et al (2007), Brenguier et al (2008a), Wegler et al (2009), Nakata & Snieder (2011), Takagi et al (2012), Hobiger et al (2012), Richter et al (2014) and other authors. In particular, Richter et al (2014) showed that the amplitude of the velocity drop after an earthquake is proportional to the local peak ground acceleration (pga).…”
mentioning
confidence: 94%
“…The possible physical mechanisms causing this behaviour are discussed in Rubinstein & Beroza (2004a) and Wegler et al (2009). A static coseismic stress change would lead to increases and decreases of stress in different regions depending on the source mechanism.…”
Section: Transient Velocity Changesmentioning
confidence: 99%
“…Wu et al [2009] use a single station located on a soft rock site and do not average over several months. Wegler et al [2009] estimate the velocity reduction in deeper parts of the subsurface, and the velocity reduction they find is small (0.3-0.5 %). From this we infer that the velocity reduction due to a major earthquake is most pronounced in near surface, especially for soft rock sites.…”
Section: Influence Of Major Earthquakesmentioning
confidence: 99%
“…By using these networks for seismic interferometry, Tonegawa et al [2009] extract the deep subsurface structure of the Philippine Sea slab. These data have also been used to observe time lapse changes in small regions [Wegler and Sens-Schönfelder, 2007;Sawazaki et al, 2009;Wegler et al, 2009;Yamada et al, 2010]. Each KiK-net station has two receivers, one on the ground surface and the other at the bottom of a borehole.…”
Section: Introductionmentioning
confidence: 99%